Marine pollution from antifouling paint particles - Turner, Andrew (Marine pollution bulletin, 2010)
Antifouling paint particles (APP) are generated during the maintenance of boats and are shed from abandoned structures and grounded ships. Although they afford a highly visible, colourful reflection of contamination in the vicinity of the source, little systematic study has been undertaken regarding the distribution, composition and effects of APP in the wider marine environment. This paper reviews the state of knowledge in respect of APP, with particular emphasis on those generated by recreational boatyards. The likely biogeochemical pathways of the biocidal and non-biocidal metals in current use (mainly Cu and Zn) are addressed in light of recent research and an understanding of the more general behaviour of contaminants in marine systems. Analyses of paint fragment composites from recreational facilities in the UK reveal chemical compositions that are similar to those representing the net signal of the original formulations; significantly, dry weight concentrations of Cu and Zn of up to about 35% and 15%, respectively, are observed and, relative to ambient dusts and sediment, elevated concentrations of other trace metals, like Ba, Cd, Cr, Ni, Pb and Sn, occur. These metals leach more rapidly from APP than a painted surface due to the greater surface area of pigments and additives exposed to the aqueous medium. In suspension, APP are subject to greater and more rapid environmental variation (e.g. salinity, pH, dissolved oxygen) than painted hulls, while settled APP represent an important source of persistent and degradable biocides to poorly circulating environments. Through diffusion and abrasion, high concentrations of contaminants are predicted in interstitial waters that may be accumulated directly by benthic invertebrates. Animals that feed non-selectively and that are exposed to or ingest paint-contaminated sediment are able to accelerate the leaching, deposition and burial of biocides and other substances, and represent an alternative vehicle for contaminant entry into the marine foodchain. Clearly, an extensive understanding of biocide behaviour on painted surfaces is not sufficient for predictive or management purposes regarding APP. Greater caution is required by boaters and boatyards during the removal and disposal of solid wastes, and more awareness or stricter enforcement of relevant codes of practice or legislation is recommended.